2023
DOI: 10.1021/acs.iecr.3c01700
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effective and Ecologically Sustainable Carbon Nano-Onions for Antibiotic Removal from Wastewater

Poonam Kumari,
Kumud Malika Tripathi,
Kamlendra Awasthi
et al.

Abstract: The discharge of antibiotics into the aquatic environment can become toxic and hazardous to both human health and the environment. Therefore, it is enormously essential to remove multiple antibiotics from the wastewater. In this work, carbon nano-onions (CNOs) were synthesized and used as effective adsorbents for the removal of 97% norfloxacin (NOR) and 99% tetracycline hydrochloride (TCH) antibiotics from wastewater. CNOs showed good adsorption efficiency, and the equilibrium period was also short. The adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…It was observed that in the initial stage, there was a quick rise in the removal efficiency by N-CA, then reached a plateau after ∼40 min. 68 This rapid adsorption at the initial stage can be because of the complete availability of the number of active sites on N-CA for the adsorption of ASP and PCM. However, after some time the number of available active sites on N-CA became gradually filled with ASP and PCM.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that in the initial stage, there was a quick rise in the removal efficiency by N-CA, then reached a plateau after ∼40 min. 68 This rapid adsorption at the initial stage can be because of the complete availability of the number of active sites on N-CA for the adsorption of ASP and PCM. However, after some time the number of available active sites on N-CA became gradually filled with ASP and PCM.…”
Section: Resultsmentioning
confidence: 99%
“…Following the previously reported flame pyrolysis approach, carbon nano-onions (CNOs) were synthesized from used frying oil 27 . In a typical procedure, cotton wick was used to ignite waste frying oil in a clay lamp.…”
Section: Methodsmentioning
confidence: 99%
“…PPCPs are the class of emerging pollutants which includes drugs, antibiotics, 68 hormones, fragrances, cosmetics, and sunscreen agents. 69 PPCPs enter the environment through various natural and anthropogenic activities.…”
Section: Emerging Pollutants and Their Detection Using Graphene Aerogelsmentioning
confidence: 99%